Anthropometry and biochemical assessments of women of childbearing age and children 6–59 months of age from rural areas in Akwa Ibom State, Nigeria - Maziya-Dixon, B.; Sanusi, R. A.; Oguntona, E. B. (International Institute of Tropical Agriculture, 2021)
The Nutrition Survey was a project in Akwa Ibom State looking at the nutritional status of children 6-59 months and their mothers (women of childbearing age) through biological sample collection and anthropometric measurements to assess the extent of malnutrition and micronutrient deficiencies, especially in vitamin A and iron. A listing of all local government areas was obtained, grouped according to the level of urbanization as defined by the Federal Government of Nigeria. The current official designation of rural, medium, and urban is based mainly on population. A community with fewer than 5000 people is regarded as rural, 5000-20000 as medium, and more than 20000 as urban. A total of 10 Local Government Areas (LGAs) were selected using the probability proportionate to size sampling technique so that the likelihood of an LGA being selected is proportional to its population size. A total of 570 households were selected with women of childbearing age and children 6-59 months of age making a total of 1,140 participants.